1975
DOI: 10.1029/wr011i004p00581
|View full text |Cite
|
Sign up to set email alerts
|

Identification of parameters in a linear equation of groundwater flow

Abstract: An inductive method is presented for evaluating parameters in a two-dimensional linear equation describing groundwater flow. The approach employs finite difference approximations, which can be simply programed for calculation by computer. Before illustrating the method, which is applicable to both stationary and time-dependent problems, the various types of data required for evaluation in general are systematically enumerated. An assumption is introduced limiting the local variability of T, the transmissivity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1975
1975
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…Cooley and Sinclair [1976] have stated that normal methods of contouring data manually also tend to smooth out permeability contrasts. In addition, experience with the direct solution proposed by Nutbrown [1975] has shown that the predicted values of transmissivity and storage coefficient are generally realistic but that discretization of boundary conditions such as occur at streams and leaky rivers is particularly difficult and may lead to unreasonable values of the computed aquifer properties. Neuman [1975] has shown that measured hydraulic heads rarely satisfy the assumed flow equation, which usually includes Depuit's assumption, and that employment of direct methods with an inadequate flow equation can induce errors in the computed aquifer parameters which overshadow their true values.…”
Section: Introductionmentioning
confidence: 99%
“…Cooley and Sinclair [1976] have stated that normal methods of contouring data manually also tend to smooth out permeability contrasts. In addition, experience with the direct solution proposed by Nutbrown [1975] has shown that the predicted values of transmissivity and storage coefficient are generally realistic but that discretization of boundary conditions such as occur at streams and leaky rivers is particularly difficult and may lead to unreasonable values of the computed aquifer properties. Neuman [1975] has shown that measured hydraulic heads rarely satisfy the assumed flow equation, which usually includes Depuit's assumption, and that employment of direct methods with an inadequate flow equation can induce errors in the computed aquifer parameters which overshadow their true values.…”
Section: Introductionmentioning
confidence: 99%
“…This coastal aquifer is typical of many encountered in semiarid regions in that recharge is restricted to known localized areas and although variable, follows a cyclical pattern. This last condition often allows a steady state formulation to be used (Nutbrown, 1975) and, in the case of the method described here, leads to estimates of the average recharge given average water levels.…”
Section: The Example -Oman Coastal Plainmentioning
confidence: 99%
“…The method outlined in this paper is particularly applicable to those semiarid regions where recharge, although variable, follows a cyclical pattern thus allowing a steady state formulation (Nutbrown, 1975) . The partial differential equation describing steady state groundwater flow can be approximated by a set of simultaneous equations with recharge as the dependent variable, water levels as the independent variable and the parameter of transmissivity as the coefficient matrix linking the two.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nelson [5] has devised a method for integrating the homogeneous version of (1) (i.e.,/ = 0) along its characteristics, and Frind and Pinder [3] have developed a finite element Galerkin technique. A finite difference approach has also been proposed by Nutbrown [6].…”
Section: Introduction the Partial Differential Equationmentioning
confidence: 99%